Legends of CHIMA [videorecording (DVD)] : CHI, tribes, and betrayals. (Warner Bros. Entertainment Inc., 2014)
Once a pristine, natural paradise, the Kingdom of CHIMA has become a battle ground for eight animal tribes. Best friends are now enemies. The animals fight for control of a natural resource called CHI, a powerful element that is both a source of life and potential destruction. Only a few brave heroes in CHIMA understand the true nature of CHI, and the possible downfall of CHIMA that will result from its misuse.